Integrative Analysis of VEGFA Gene Expression and Drug Targeting in Kidney Renal Clear Cell Carcinoma (KIRC - AMUKTI, DANANG; Ria Indah Pratami, (Scripta Medica, 2026)
Background/Aim: Vascular endothelial growth factor A (VEGFA) plays an important role in angiogenesis and is known to have a strong association with the development of various types of cancer, including kidney renal clear cell carcinoma (KIRC). The purpose of this study was to analyse VEGFA expression in KIRC tissue, identify genes that have high expression correlation and explore the therapeutic potential of VEGFA through the identification of drugs that target it. Methods: This study used a public data-based bioinformatics approach to evaluate VEGFA gene expression, identify genes that have similar expression patterns (co-expression) with it and examine the potential of drugs targeting VEGFA in KIRC. Data and analysis were obtained from various trusted databases, namely UALCAN, GEPIA, TCGA, TISIDB and DrugBank.Results: VEGFA was found to be significantly higher expressed in KIRC tissue compared to normal tissue. Ten genes showed high expression correlation with VEGFA, namely RP1-261G23.7, FLT1, ZNF395, COL23A1, RP11-255M6.1, PLVAP, EXOC3L2, ESM1, EGLN3 and HIF1A-AS2. In addition, VEGFA is known to be the target of various therapeutic agents such as ranibizumab, VEGF-AS, bevasiranib, gliclazide, SNS-032, denibulin, aflibercept, ABT-510, dalteparin and chondroitin sulphate, most of which have a mechanism of action in inhibiting angiogenesis. Conclusion: VEGFA has the potential to be an important biomarker and therapeutic target in KIRC. The combination of gene expression analysis and drug data confirms the strategic value of VEGFA in the development of more effective antiangiogenic therapies.